2018
DOI: 10.1155/2018/4153464
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on Deformation Mechanism of Grain Boundaries in Magnesium Crystal: Based on Coincidence Site Lattice Theory

Abstract: As for magnesium (Mg) alloys, it has been noted that they are inferior to plastic deformation, but improvement in the mechanical properties by further refinement of grain size has been recently suggested. It means the importance of atomistic view of polycrystalline interface of Mg crystal. In this study, to discuss the deformation mechanism of polycrystalline Mg, atomistic grain boundary (GB) models by using coincidence site lattice (CSL) theory are constructed and are simulated for their relaxed and deformatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Due to the complexity of the HCP structure, little research has been done on polyMg and its composites. Saitoh et al [13] established grain boundary (GB) models of Mg crystal to study the deformation mechanism under uniaxial tension by the MD method. The results showed that there are significant differences in the deformation mechanisms of GBs from different angles.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the HCP structure, little research has been done on polyMg and its composites. Saitoh et al [13] established grain boundary (GB) models of Mg crystal to study the deformation mechanism under uniaxial tension by the MD method. The results showed that there are significant differences in the deformation mechanisms of GBs from different angles.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the (0001) plane of sapphire (Al 2 O 3 ) and (111) plane of NbC was investigated to explain the observation that NbC on c-plane sapphire grows preferentially with the (111) plane. The coincident site lattice (CSL) [31][32][33][34] or domain-matching epitaxy (DME) theory [35][36][37][38] shows that the NbC (111) plane could grow epitaxially on the Al 2 O 3 (0001) plane. Figure 4a, the f value is reduced to 0.16; therefore, an epitaxial growth can be expected.…”
Section: Epitaxial Growth Mechanismmentioning
confidence: 99%
“…Among these are investigations into pure metals such as sodium [8][9], potassium [10], rubidium [11], and binary metals-alloys [8,12]. Recently, MD simulation technique has become a useful tool to study the mechanical properties and deformation behavior of materials at the nano or atomistic regime [13][14][15]. Heino et al [16], simulated strain on a single Cu crystal for various orientations using MD simulations.…”
Section: Introductionmentioning
confidence: 99%